CSIG-30. EPIGENETIC REACTIVATION OF BAI1 BLOCKS ONCOGENIC IGF1R SIGNALLING IN MEDULLOBLASTOMA. (14th November 2022) - Yamamoto, Takahiro; Osuka, Satoru; Van Meir, Erwin
Abstract: Medulloblastoma (MB) is the most aggressive pediatric brain tumor and a better understanding of this disease is warranted to develop new therapeutic approaches. Brain-specific Angiogenesis Inhibitor 1 (BAI1/ADGRB1) is an orphan seven-transmembrane G protein-coupled receptor predominantly expressed in the brain and epigenetically silenced in MB formation. MDM2 is an E3 ubiquitin ligase that leads to the proteosomal degradation of multiple proteins. We previously found that BAI1 can prevent MDM2 nuclear activity by trapping it at the cell surface, and in the process suppress tumor formation by stabilizing p53. Since MDM2 also ubiquitinates cell surface proteins, we hypothesized that its membrane trapping might increase the degradation of oncogenic tyrosine kinase receptors. To explore this idea, we examined IGF1R, a known cell surface MDM2 target and found that BAI1 negatively regulates IGF1R at the protein level. In contrast, BAI1 expression did not change the protein expression levels of other RTKs (INSR, EGFR). Using co-immunoprecipitation assays we confirmed that MDM2 interacts with both BAI1 and IGF1R in MB cells. In addition, the interaction between IGF1R and β-Arrestin, which is crucial for ubiquitination and down-regulation of IGF1R by acting as an adaptor for MDM2, was increased with BAI1 expression. To examine the impact of BAI1 overexpression on IGF1 receptor signaling, we examined its downstream signaling mediators (Stat3, Akt, Erk). Stat3 and Akt phosphorylation were suppressed upon BAI1 expression, while Erk signaling was activated but through a mechanism independent from IGF1R expression. As IGF1R is known to drive radiation resistance, we examined whether BAI1 could radiosensitize the cells and found that this was indeed the case. Altogether, our data indicate that reactivating BAI1 in MB has dual anti-tumor effects by stabilizing p53 and blocking IGF1R signalling.